Effect of Particles Size on EFB Bio-briquettes of Calorific Value - Nofriady Handra; Anwar Kasim; Gunawarman (Jurnal Teknik Mesin, 2017)
The development of biomass has been assumed as an important issue in the past several decades and would remain to be attractive in the future due to its clean, renewable, and carbon–neutral properties. Biomass is one of the most important renewable energy resources in the world. In recent decades, the utilization of biomass has dramatically increased. The objective of this research was to knowing effect of particles size on EFB bio-briquettes of calorific value. There were many reasons. First, biomass is a renewable resource, because of the availability of biomass is unlimited, and its regenerative process runs well. Second, the extraction of biomass energy can be carried out more flexibly. The biomass can be burned directly without high technology. Biomass bio-briquettes are often used as an energy source for cooking purpose and in some industries. The 2% (dry basis) is used as a binder in a mixture with EFB fibre. Samples of solid cylindrical shape Ø 4 cm and 6 cm high and density sample is 0,8 g/cm2. The pressure is used to generate samples specified in the mold volume. The volume of the cylinder is 75,36 cm2. The particle size briquette of 40 mesh average water content of 9,1% was generated while the size of 60 mesh was 9,5%. The particle size of 60 mesh (smooth) yields the highest value between 20 mesh and 40 mesh. The value of ash content generated by 4,35% is higher than the size of 20 mesh (2,88%) and 40 mesh (3,09%). On the particle size of 20 mesh fibers (more roughly), it yields a calorific value of 4237,5 kal /g and is higher than 40 mesh fiber particle size (4102,2 kal/g) and 60 mesh (4066,5 kal/g). The difference in heating value produced by the three did not show any significant difference.